The Role of Social Support and Resilience in Prison Inmates: Literature Study - Gemilang Dian Permata Artika Sari; Paulina Kurniadi; Siti Muslimah; Dian Veronika Sakti Kaloeti; Hastaning Sakti (International Journal Labs, 2022)
People who violate legal norms and are sentenced to criminal penalties will live their daily lives in Correctional Institutions whose conditions are much different from people's lives. So it requires resilience and social support in undergoing detention. This study aims to determine the role of social support and resilience in research. This study uses a literature study method by reviewing research articles from 2012 to 2021 visited at Springer Link, Science Direct, Semantic Scholar, and Google Scholar. From the search results on four search sources, 10 relevant journals are obtained for further review. The articles reviewed are in English, research participants are prisoners, use a quantitative research design, and focus on social support and resilience in research. From ten journals reviewed, the key is that resilience has an important role in life in prison and can be influenced by several factors, namely support from the environment, spirituality, self-esteem, and self-acceptance. Social support is important for work to facilitate the transition, and avoid recidivism and is very helpful for reducing health morbidity, life satisfaction, and social adjustment to prison. Resilience and social support are protective factors for the mental health of prisoners while in prison, and resilience can mediate the relationship between social support and mental health.